PENGARUH FAKTOR PRODUKSI TERHADAP PRODUKSI KELAPA HIBRIDA POLA PLASMA DI KABUPATEN INDRAGIRI HILIR - Eliza '; Suardi Tarumun; Yusmini ' (Fakultas Pertanian, Universitas Riau, 2010)
The purposes of this research were to identify : 1) impact of production factors, (plantation area,fertilizer, pesticide, number of trees, and labor) on production of coconut nucleus estate, 2)return to scale of coconut nucleus estate, 3) efficiency of production factors used, and 4)farmers’ problems in managing business. This research was conducted in Pulau BurungRegency, Indragiri Hilir District, the only Nucleus Estate of hybrid coconut tree program inIndonesia. Primary data were collected from 90 respondents. Results showed that productionfactors of fertilizer and labor significantly affected production of coconut trees withdetermination coefficient of 79,3 %. Each of these factors influenced the production at differentrate. Total coefficient of production elasticities was 1.307, indicated that production process wasin the area of increasing to scale. However, because marginal product value were 0,081 forfertilizer and 0,193 for labor, further increase of production factor use is not economicallyfeasible. This is due to coconut price which is much less than market price. The farmers’problems are lack of capital to support production, high prices of inputs while coconut price islow. The research recommended that government increases support in term of input subsidies,community development and partnership, farmer credit scheme with low interest, and review ofcurrent predetermined and regulated price of fresh coconut.